Oral Administration of a Phage Cocktail to Reduce Salmonella Colonization in Broiler Gastrointestinal Tract—A Pilot Study - Wattana Pelyuntha; Ananya Yafa; Ruttayaporn Ngasaman; Mingkwan Yingkajorn; Kridda Chukiatsiri; Nidanut Champoochana; Kitiya Vongkamjan (Animals, 2022)
Salmonella contamination in poultry meat products can lead to serious foodborne illness and economic loss from product recalls. It is crucial to control Salmonella contamination in poultry from farm to fork. Bacteriophages (phages) are viruses of bacteria that offer several advantages, especially their specificity to target bacteria. In our study, three Salmonella phages (vB_SenS_KP001, vB_SenS_KP005, and vB_SenS_WP110) recovered from a broiler farm and wastewater treatment stations showed high lysis ability ranging from 85.7 to 96.4% on over 56 serovars of Salmonella derived from several sources, including livestock and a broiler farm environment. A three-phage cocktail reduced S. Enteritidis and S. Typhimurium, in vitro by 3.9 ± 0.0 and 3.9 ± 0.2 log units at a multiplicity of infection (MOI) of 103 and 3.8 ± 0.4 and 4.1 ± 0.2 log units at MOI of 104 after 6 h post-phage treatment. A developed phage cocktail did not cause phage resistance in Salmonella during phage treatments for three passages. Phages could survive under simulated chicken gastrointestinal conditions in the presence of gastric acid for 2 h (100.0 ± 0.0% survivability), bile salt for 1 h (98.1 ± 1.0% survivability), and intestinal fluid for 4 h (100 ± 0.0% survivability). Each phage was in the phage cocktail at a concentration of up to 9.0 log PFU/mL. These did not cause any cytotoxicity to human fibroblast cells or Caco-2 cells as indicated by the percent of cell viability, which remained nearly 100% as compared with the control during 72 h of co-culture. The phage cocktail was given to broilers raised in commercial conditions at a 9 log PFU/dose for five doses, while naturally occurring Salmonella cells colonized in the gastrointestinal tract of broilers were significantly reduced as suggested by a considerably lower Salmonella prevalence from over 70 to 0% prevalence after four days of phage treatment. Our findings suggest that a phage cocktail is an effective biocontrol agent to reduce Salmonella present in the guts of broilers, which can be applied to improve food safety in broiler production.